APPLICATION OF FISHER’S CRITERION TO ENSURE THE RESULTS OF THE STUDENTS RESIDUAL EVALUATION - Sachaniuk-Kavets’ka, N.; Kavetskiy, V. (Physical and Mathematical Education, 2021)
Formulation of the problem. In modern pedagogical research, a special place is occupied by residual knowledge of academic disciplines, which are fixed in the memory of students at fairly long intervals, but whose role is decisive in their formation as specialists. The problem of reliability of the results of assessment of residual knowledge of students is relevant, because these results are the source information for optimization and modernization of the educational process. In view of the above, it is necessary to find out the possibility of comparing the performance of students of different years who studied in the same conditions on residual knowledge, to choose the criterion of such comparison and to find out whether this knowledge is a constant value. Materials and methods. To perform the research tasks, the following methods were used: analysis, synthesis, comparison, systematization and generalization of educational-methodical and popular science sources on the research problem, pedagogical experiment, primary statistical processing and generalization of the obtained data. The study was conducted on the basis of Vinnytsia National Technical University at the Department of Higher Mathematics. Results. In the analysis of residual knowledge on the basis of KKR for the purpose of further adjustment of forms, methods and means of training special methods of their processing are applied, possibility of application of Fisher’s criterion (angular Fisher’s transformation) for an estimation of presence (absence) of real difference in levels of preparation of student groups under the same conditions. Conclusions. To ensure a sound decision, it is advisable to apply the Fisher test, which will assess the real difference in the levels of preparation of student groups who studied in the same conditions, but differ in the number of students in the group. Analyzing the statistical coefficients, it can be argued that the level and quality of residual knowledge remains constant, regardless of whether students taught this material last semester or last year. A broader grading scale, rather than the traditional five-point scale, should be used to more clearly define the level of this knowledge.